The effects of sleep deprivation on spatial memory, dream and hyperphosphorylated tau proteins expression in rats - Ramli, Norhida (2021)
Circadian rhythm is regulated by an endogenous biological regulator controlling various physiological activities, including cell cycle, body temperature, and metabolism. Some consolidation of memory occurs during Rapid Eye Movement (REM) sleep, so when the circadian system breaks down and REM sleep depressed, the memory will be affected. Downstream regulatory modulator antagonist (DREAM) proteins were discovered to affects learning and memory, while Tau protein hyperphosphorylation indicates some degree of neuronal instability influencing learning processes. This study aimed to examine the effects of sleep and circadian disruption (CD) on memory. One hundred and fourty four Sprague Dawley rats were used in this study. In the CD experiment, acute circadian disruption (ACD) was induced by putting the rats on a three-hour phase advance method for 6 days followed by 10 days of re-entrainment. This cycle was induced four times in a chronic circadian disruption (CHCD) study. On the other hand, REM sleep deprivation was induced by putting the rats on a small platform in a water tank (REMsd group). The REMsd control group (PC) was placed in the same condition as the REMsd group except that they were put in a broader platform to sleep and relax (PC group). The free-moving control group (CC) was placed in normal propylene cages (CC group). It was followed by the Morris water maze (MWM) task to assess spatial, probe test, and reverse spatial test. Then, the rat’s brain from the hippocampal region was removed. The neuron's nucleus and cytoplasm were extracted for DREAM, normal Tau, and phosphorylated Tau protein expression analyses by Immunohistochemistry and Western Blot (WB) analysis. In MWM test, the mean daily escape latency was measured for all rats from each group. The differences of EL between the groups were not statistically significant (p > 0.05) when compared between all groups in REM and CD experimental groups. The probe test showed no statistically significant (p>0.05) difference between the groups in the REMsd and CD experiment. The reverse spatial trial showed no significant difference between all groups (p>0.05) in the REMsd and CD experiment. DREAM protein expression was not statistically significant difference between groups in the REMsd and CD experiment. Tau and phosphorylated Tau protein was found to be significantly different when compared between REMsd and CC groups (p<0.05) and ACD and CCD group in the REMsd and CD experiment, but not significant difference for hyperphosphorylated Tau protein expression. WB analysis showed that the mean relative DREAM protein level was not statistically significant between all groups in the REMsd and CD experiment groups. The mean relative hyperphosphorylated Tau difference also was found not statistically significant between groups in the REMsd and CD experiments. In conclusion, the current study protocol failed to adequately elicited significant changes in neurobehavioral and level of the DREAM and hyperphosphorylated Tau protein expression.